Chemical Analysis Methods to Detect Pork DNA and Derivative Contents in Food: A Review - Berti, Lusiana; Yetti, Rina Desni; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Purpose: Indonesia is a country which the most Muslim population in the world. In Indonesia, Halal in food product are mainly priority. Food adulteration with elements of pork or its derivatives become a very important thing to be analyzed. Therefore, There are several analytical methods that can be used such as molecular biology techniques including PCR, FTIR, chromatography, and electronic nose. This method can provide information to the public in choosing food products that are halal and tested. This review article describes the analytical methods that can be used for determination pork contents and its derivatives using various methods. Selection of Data Sources: In preparing this article review, literature study techniques was used by using primary data from international journals. The data was searched by used online media such as ScienceDirect, NCBI, Research Gate, Google Scholar, Pub Med, and E-Resources. Conclusion: PCR method was the best method. It was sensitive, specific, simple, and economical. This method was suitable for confirm authenticity of food and detected of pork DNA in food products.